Oxygen enhanced lung MRI by simultaneous measurement of T1 and T2* during free breathing using ultrashort TE. Issue 6 (7th July 2014) - Triphan, Simon M.F.; Breuer, Felix A.; Gensler, Daniel; Kauczor, Hans‐Ulrich; Jakob, Peter M.
<x xml:space="preserve">Abstract</x> Purpose To provide a robust method for the simultaneous quantification of T1 and T2* in the human lung during free breathing. Breathing pure oxygen accelerates T1 and T2* relaxation in the lung. While T1 shortening reflects an increased amount of dissolved molecular oxygen in lung tissue, T2* shortening shows an increased concentration of oxygen in the alveolar gas. Therefore, both parameters reflect different aspects of the oxygen uptake and provide complementary lung functional information. Materials and Methods A segmented inversion recovery Look–Locker multiecho sequence based on a multiecho 2D ultrashort TE (UTE) was employed for simultaneous T1 and T2* quantification. The radial projections follow a modified golden angle ordering, allowing for respiratory self‐gating and thus the reconstruction of a series of differently T1 and T2*‐weighted images in arbitrary breathing states. The method was evaluated in nine healthy volunteers while breathing room air and pure oxygen, with two volunteers examined at five oxygen concentrations. Results Relative differences of ΔT1 between 7.9% and 12.7% and of ΔT2* between 13.2% and 6.0% were found. Conclusion The proposed method provides inherently coregistered, quantitative T1 and T2* maps in both expiration and inspiration from a single measurement acquired during free breathing and is thus well suited for clinical application.J. Magn. Reson. Imaging 2015;41:1708–1714. © 2014 Wiley Periodicals, Inc.